Desmoid tumors: old and new drugs for a rare and challenging disease - Kasper, Bernd (Cancer, 2025)
There has been a paradigm shift in the treatment strategy for patients with desmoid tumor toward less invasive management using systemic therapies. In addition to older drugs, such as conventional chemotherapy and tyrosine kinase inhibitors, the newest class of medical agents—the gamma secretase inhibitors—have been included in the treatment armamentarium for patients with desmoid tumor, as nicely depicted in the latest consensus guideline from The Desmoid Tumor Working Group.
Erstmals veröffentlicht: 15. November 2024
Gesehen am 08.05.2025